Factors Affecting Oral Hygiene Behavior in 9-12-Year-Old Children Based on Data from Fars Birth Cohort Study - Mohsen Sharif Zadeh Ardakani; Sulmaz Ghahramani; Seyed Taghi Heidari; Maryam Bakhtiar; Parissa Sadat Ghoreishi; Kamran Bagheri Lankarani (Shiraz University of Medical Sciences, 2024)
Background: Several factors may influence oral hygiene behavior, which is essential for oral health and well-being in children. This study aimed to investigate the factors that contribute to the oral hygiene behaviors in children, especially mothers' oral hygiene behaviors.Methods: In this cross-sectional study, data from the fifth phase of Fars Birth Cohort Study were used. Our focus was on a group of 1143 children aged 9-12 years old in the year 2021. The demographic, socio-economic variables as well as oral hygiene behaviors of children and their mothers were assessed. The score for oral hygiene behavior was determined based on self-reported practices of brushing, flossing, and mouthwash, ranged between 0 and 3. The factors related to children's oral hygiene behavior were examined by logistic regression analysis.Results: In this study, 345 (30.2%) of the children (50.3% females, average age 10.33±0.48 years) did not brush their teeth, 1042 (91.2%) did not use dental floss, and 1083 (94.8%) did not use mouthwash. The mean score for oral hygiene behavior in children was 0.83±0.67. Mothers had a higher mean score of 1.42±0.74 (P<0.001). Several factors were found to be significantly associated with oral hygiene behavior in children, including higher scores for mothers' oral hygiene behavior (OR=2.18, P<0.001), living in the center of the province (OR=0.73, P=0.04), having insurance (OR=1.47, P=0.03), and having a government-employed mother (OR=0.52, P=0.025). Children with regular six-monthly or yearly visits had higher odds compared with those who visited the dentist only when a problem arose (OR=7.27, P=0.009, and OR=2.33, P=0.01, respectively).Conclusion: The study revealed unacceptable oral hygiene behaviors in 9-12-year-old children, and showed the gap between oral hygiene behavior in mothers and children. The mother's role in promoting oral health and hygiene is crucial. Future research should consider mediating and confounding impacts of knowledge, attitudes, and practices related to oral hygiene.